Generalized method for evaluation of the mutual coupling effect on the radiation and scanning characteristics of microstrip array antenna - Ali Abdul Amir M.; Vishvakarma Babau R. (My University, 2025)
Based on a cavity model, the microstrip antennas are analyzed using the dyadic Green's function to obtain the far-field radiation. Because of mutual coupling effects, the input impedance of a radiating antenna in an array is different from its impedance value when it is isolated, and this difference varies with the angle of scan of the array. The mutual coupling between the two patch elements decreases when the spacing between them increases.